2023
DOI: 10.4236/jwarp.2023.156017
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Picocyanobacteria (Order <i>Synechococcales</i>) and Occurrence of the Cyanotoxin Anatoxin-A in a Shallow Mesotrophic Pond

Abstract: We have verified the use of a serial filtration method to isolate picocyanobacteria for analysis. We used eDNA metabarcoding to confirm the picocyanobacteria as members of the Order Synechococcales, Genus Cyanobium, specifically Cyanobium 6307. Fluorometric analysis using accessory pigments phycocyanin and phycoerythrin described periods of excess biomass, where the net growth rate model confirmed these conditions. The total anatoxin-a concentrations in the picocyanobacterial sample ranged from 0.0074 -6.41 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Recent genomic [6] and 16s metabarcoding [7] analysis has confirmed that commonly found picocyanobacteria (Order Synechococcales) can produce anatoxin-a. As described elsewhere [7], the presence of (pico)cyanobacteria can be heavily influenced by salinity.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Recent genomic [6] and 16s metabarcoding [7] analysis has confirmed that commonly found picocyanobacteria (Order Synechococcales) can produce anatoxin-a. As described elsewhere [7], the presence of (pico)cyanobacteria can be heavily influenced by salinity.…”
Section: Introductionmentioning
confidence: 94%
“…Samples of whole lake water (WLW) and net (NET) water samples were collected from five different sites representing a range of saline environments on a series of dates between May and October from the shoreline (maximum depth 1m) (Figure 1 brown amber bottles, placed on ice and transported to the laboratory for further analysis. Size fractionation using floatation, serial filtration with gravity and serial filtration with pressure were used for sample processing and collection [7].…”
Section: Field Samplingmentioning
confidence: 99%
See 3 more Smart Citations